2017
DOI: 10.24170/13-1-1686
|View full text |Cite
|
Sign up to set email alerts
|

ASD and PDA closure with CeraTM and CeraFlexTM devices

Abstract: We discuss our experience using the new Cera TM and Ceraflex TM (Lifetech, Nashan, Shenzhen, China) devices in closing PDAs, an ASD and PFOs. PATIENTSThis is a retrospective review of lesions closed using the Cera ABSTRACTASD AND PDA CLOSURE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Incorrect device selection, as well as the inappropriate placement of the device, may play a role. There are many reports of the embolisation of various devices in the literature but the only report about the embolisation of the CeraFlex TM PDA occluder that we could find in the literature was in the study of Buys et al 26 They reported their experience with the CeraFlex TM PDA occluder in 12 patients and Cera TM occluder in 4. They used a 04/06 mm device in seven patients (58.4%), 08/10 mm in three (25%), and 06/08 mm in two (16.6%) in the CeraFlex TM occluder group.…”
Section: Discussionmentioning
confidence: 97%
“…Incorrect device selection, as well as the inappropriate placement of the device, may play a role. There are many reports of the embolisation of various devices in the literature but the only report about the embolisation of the CeraFlex TM PDA occluder that we could find in the literature was in the study of Buys et al 26 They reported their experience with the CeraFlex TM PDA occluder in 12 patients and Cera TM occluder in 4. They used a 04/06 mm device in seven patients (58.4%), 08/10 mm in three (25%), and 06/08 mm in two (16.6%) in the CeraFlex TM occluder group.…”
Section: Discussionmentioning
confidence: 97%
“…10,11 There are some techniques performed by institutes and operators individually to reduce the risk of device protrusion or to correct the protruded device, such as balloon repositioning of the device 7,8 or supporting the device by a pigtail catheter during release. 12 To our knowledge, there has been no report about balloon-assisted device releasing technique in the literature. The aim of this study is to present our experience with this technique and its benefits on reducing the risk of device protrusion and complications related to protrusion.…”
mentioning
confidence: 99%